2013 International Conference on Advanced Computer Science Applications and Technologies 2013
DOI: 10.1109/acsat.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Older People and the Use of Mobile Phones: An Interview Study

Abstract: Ageing populations are turning to technology in greater numbers than ever. New technology is being designed to help older people live independently for longer. Despite the usefulness of mobile phones especially older people, the current problems with its complex features and interface designs have intimidated some older people users from using the device. The authors wished to explore exposure to the real-world technology needs of older people by evaluating the mobile phones use among them. Although numerous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…27 Accordingly, we adopted in-depth telephone interviews as a tool of inquiry. 28 Through the telephone, interviewers personally engaged with older persons to elicit experiential accounts of their coping strategies during the lockdown. Qualitative research is a social-constructionist tradition of data collection; hence, it is apt for the contextual understanding of personal experiences and allows for processing instrumental narratives.…”
Section: Methodsmentioning
confidence: 99%
“…27 Accordingly, we adopted in-depth telephone interviews as a tool of inquiry. 28 Through the telephone, interviewers personally engaged with older persons to elicit experiential accounts of their coping strategies during the lockdown. Qualitative research is a social-constructionist tradition of data collection; hence, it is apt for the contextual understanding of personal experiences and allows for processing instrumental narratives.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, there are suggested that many older people are more comfortable using simpler designs [9], [10]. The design and development of ICT product must support the elderly end users, especially to overcome their feelings of fears and enable them to accept technological aids and mobile devices in their lives [11]. Mobile apps with simple design attract users as they do not require complex interactions.…”
Section: Background and Related Studiesmentioning
confidence: 99%
“…Indeed, there are suggested that many older people are more comfortable using simpler designs [9], [10]. The design and development of ICT product must support the elderly end users, especially to overcome their feelings of fears and enable them to accept technological aids and mobile devices in their lives [11]. Mobile apps with simple design attract users as they do not require complex interactions.…”
Section: Background and Related Studiesmentioning
confidence: 99%